2007
DOI: 10.1096/fj.07-9909com
|View full text |Cite
|
Sign up to set email alerts
|

Identification, classification, and expression ofRAGEgene splice variants

Abstract: The receptor for advanced glycation end-products (RAGE) is a single-transmembrane, multiligand receptor of the immunoglobulin superfamily. RAGE up-regulation is implicated in numerous pathological states including vascular disease, diabetes, cancer, and neurodegeneration. The understanding of the regulation of RAGE is important in both disease pathogenesis and normal homeostasis. Here, we demonstrate the characterization and identification of human RAGE splice variants by analysis of RAGE cDNA from tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
370
1
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(399 citation statements)
references
References 30 publications
19
370
1
9
Order By: Relevance
“…Indeed, the regulatory mechanisms for proteolytic shedding of cellbound RAGE to generate sRAGE and for alternative splicing to generate esRAGE are still unclear. Recently, new splice variants have been discovered [6] and further studies are necessary to establish which variants of sRAGE are measured by these assays and whether different soluble forms of RAGE have different (patho) physiological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the regulatory mechanisms for proteolytic shedding of cellbound RAGE to generate sRAGE and for alternative splicing to generate esRAGE are still unclear. Recently, new splice variants have been discovered [6] and further studies are necessary to establish which variants of sRAGE are measured by these assays and whether different soluble forms of RAGE have different (patho) physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cell-bound RAGE, soluble forms of RAGE appear in the plasma [4,5], as different splice variants of RAGE (e.g. endogenous secretory receptor for AGE [esRAGE]) leaking through the transmembrane and cytosolic domain [4,6], and as a proteolytically cleaved form of RAGE (sRAGE), which is most probably shed into the circulation by the sheddase, known as a disintegrin and metalloprotease 10 (ADAM 10) [7]. The functional role of these soluble forms of RAGE in the circulation remains unclear, but they may reflect the activity of the AGE-RAGE axis.…”
Section: Introductionmentioning
confidence: 99%
“…A publication summarizing the work of many laboratories showed that extensive splicing of RAGE transcripts led to as many as 20 splice variants [4]. In endothelial cells, only three isoforms of RAGE were detected at significant levels: N-truncated (Nt-RAGE), Full Length (FL-RAGE) and endogenous secretory (esRAGE).With the exception of lung tissues where constitutive expression of FL-RAGE is abundant, RAGE is expressed at low levels in most other tissues, including normal brain tissue.…”
Section: Different Isoforms Of Ragementioning
confidence: 99%
“…Over 20 different splice variants of RAGE have been identified [Hudson et al, 2008;Sparvero et al, 2009]. The RAGE gene and its exons, introns, and domains are diagrammed in Figure 1.…”
Section: Rage Signalingmentioning
confidence: 99%
“…Note the transmembrane domain and cytoplasmic tail. Derived from data in Hudson et al [2008]; Sparvero et al [2009]. signals with a complex inflammatory response that modulate their contractility.…”
Section: S100a4mentioning
confidence: 99%